Understanding the prevention of unintentional child injuries at home setting: a qualitative study in Iran - Barat, Atena (2017)
Background: Injuries include potentially life-threatening problems associated with increased hospital admission and permanent disability among children, with considerable financial, emotional and social effects on the child and the family as well as on the community and society as a whole. The preventability of injuries through adopting a variety of interventions necessitates stakeholders (e.g. parents, health professionals and policymakers) supporting and implementing such interventions. There is paucity of evidence in Iran regarding the needs for controlling home injuries among children.